Reforma del art. 133 de la Ley Orgánica de Educación Intercultural, en relación a la creación de una unidad de sustanciación de sumarios administrativos imputables a los representantes legales, directivos y docentes - Naranjo Ortiz, Gina Isabel (2014)
The Intercultural Education Law guarantees the right to education, determines the general principles and purposes that guide education in Ecuador under the Good Life, intercultural and pluri; and the relationships between its actors. It develops and deepens the rights, obligations and constitutional guarantees in education and establishes the basic regulations for the structure, levels and modes, model management, financing and participation of stakeholders in the national education system. Article 133 of the Organic Law of Intercultural Education, states that attributable to the legal representatives, principals and teachers infringements will be punished according to their severity, prior administrative proceedings, and following due process. The conduct of administrative proceedings followed the legal representatives, principals and teachers is carried out by the Human Resources Administrative Units so dispose Section 146 of the General Regulations of the Organic Law of Intercultural Education, in advance as prior actions are conducted by the District Board of Dispute Resolution or District Director , which referred the complaint or report on the presumption of the commission of a disciplinary offense by the teacher or manager should immediately refer the enabling information to Unit Human Resource management for the study and analysis of the facts allegedly accused. That is why the Human Resource Management Unit is who conducts the conduct of administrative proceedings followed the legal representatives, principals and teachers, but I believe that the right people are not because the work in the same institution become judge and part of the conduct , the burden and impartial opinion that this may imply, as the violation of the right of protection specified in Article 76 paragraph 7 ) literal k ) of the Constitution of the Republic of Ecuador to be tried by a judge or independent, impartial and competent judge , leading thus to violate the Constitution, not fulfilling the administrative proceedings will run in implementation of the guarantees of due process. Require that the administrative proceedings to ensure the right to due process and resolve them aware of another authority such as a Unit Conduct of Administrative Summaries, with power to hear and decide administrative proceedings. It should also indicate that those responsible for the Administrative Units of Human Resources in the different levels of education are people in the best trained in the Personnel Management and its role in the processing of Administrative Summaries become on Administrative Judges must act in the process. Based on the foregoing it is evident that these persons responsible for UARHs unaware of the legal procedures that must be followed to ensure due process enshrined in our Constitution.The Intercultural Education Law guarantees the right to education, determines the general principles and purposes that guide education in Ecuador under the Good Life, intercultural and pluri; and the relationships between its actors. It develops and deepens the rights, obligations and constitutional guarantees in education and establishes the basic regulations for the structure, levels and modes, model management, financing and participation of stakeholders in the national education system. Article 133 of the Organic Law of Intercultural Education, states that attributable to the legal representatives, principals and teachers infringements will be punished according to their severity, prior administrative proceedings, and following due process. The conduct of administrative proceedings followed the legal representatives, principals and teachers is carried out by the Human Resources Administrative Units so dispose Section 146 of the General Regulations of the Organic Law of Intercultural Education, in advance as prior actions are conducted by the District Board of Dispute Resolution or District Director , which referred the complaint or report on the presumption of the commission of a disciplinary offense by the teacher or manager should immediately refer the enabling information to Unit Human Resource management for the study and analysis of the facts allegedly accused. That is why the Human Resource Management Unit is who conducts the conduct of administrative proceedings followed the legal representatives, principals and teachers, but I believe that the right people are not because the work in the same institution become judge and part of the conduct , the burden and impartial opinion that this may imply, as the violation of the right of protection specified in Article 76 paragraph 7 ) literal k ) of the Constitution of the Republic of Ecuador to be tried by a judge or independent, impartial and competent judge , leading thus to violate the Constitution, not fulfilling the administrative proceedings will run in implementation of the guarantees of due process. Require that the administrative proceedings to ensure the right to due process and resolve them aware of another authority such as a Unit Conduct of Administrative Summaries, with power to hear and decide administrative proceedings. It should also indicate that those responsible for the Administrative Units of Human Resources in the different levels of education are people in the best trained in the Personnel Management and its role in the processing of Administrative Summaries become on Administrative Judges must act in the process. Based on the foregoing it is evident that these persons responsible for UARHs unaware of the legal procedures that must be followed to ensure due process enshrined in our Constitution.